2021
DOI: 10.1155/2021/9920631
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphisms of Metabolism-Related Genes with Psoriasis Vulgaris in Han Chinese

Abstract: Aim. Psoriasis is a chronic inflammatory disease with a complex etiology, and psoriasis vulgaris (PsV) is the most common type of psoriasis. Recent studies suggest the relationship between psoriasis and metabolic syndrome in different ethnicities. This study is aimed at evaluating the association of metabolism-related gene variants with the risk of PsV in Chinese Han population. Material and Methods. PsV patients (1030) and healthy controls (965) were enrolled in this study. Eighteen single-nucleotide polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…1 . Significant genes on the Manhattan plot represent each position on chromosomes 6, 10, 15, and 18 . In the genetic additive model analysis (major homo-genotype versus hetero-genotype versus minor homo-genotype), the most significant genes associated with MetS in psoriasis in GWAS analysis were the FERM domain containing 4A ( FRMD4A ), G protein-coupled receptor 116 ( GPR116 ), and mitogen-activated protein kinase 4 ( MAPK4 ) ( p <0.0001, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 . Significant genes on the Manhattan plot represent each position on chromosomes 6, 10, 15, and 18 . In the genetic additive model analysis (major homo-genotype versus hetero-genotype versus minor homo-genotype), the most significant genes associated with MetS in psoriasis in GWAS analysis were the FERM domain containing 4A ( FRMD4A ), G protein-coupled receptor 116 ( GPR116 ), and mitogen-activated protein kinase 4 ( MAPK4 ) ( p <0.0001, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies also report genetic associations between psoriasis and MetS. Liu et al 18 examined 18 SNPs previously reported to be significantly associated with MetS, and found seven which were significantly associated with psoriasis in the Han Chinese population. Abdel Hay and Rashed 19 suggested that the leptin gene ( LEP G-2548A) polymorphism could be a predictor for psoriasis and MetS among a sample of the Egyptian population, by showing that patients carrying the LEP G-2548C allele had a significantly higher prevalence of psoriasis and MetS than non-carriers.…”
Section: Discussionmentioning
confidence: 99%
“…There could be shared susceptibility genes for psoriasis vulgaris and MetS among the Chinese Han population. 5 Nevertheless, several studies have shown no genetic links between the two diseases. 45–48 …”
Section: Discussionmentioning
confidence: 99%
“…There could be shared susceptibility genes for psoriasis vulgaris and MetS among the Chinese Han population. 5 Nevertheless, several studies have shown no genetic links between the two diseases. [45][46][47][48] Clinical, Cosmetic and Investigational Dermatology 2024:17 https://doi.org/10.2147/CCID.S446966…”
Section: The Hotspots and Frontiers Close Association Of Psoriasis An...mentioning
confidence: 99%
See 1 more Smart Citation